Evaluation Of Improving Community Development And Empowerment Through Village Funds - Vinka Pebriana Parasak (ADPEBI, 2024)
This study aims to determine the use of village funds in improving development and community empowerment, as well as the impact of village funds on development and community empowerment in Maranata village, located in Sigi regency, Central Sulawesi. This study uses a qualitative descriptive approach, namely by displaying the data in the form of documents, archives and other references obtained from interviews and direct observations in the village of maranata. informants in this study were village heads, village secretaries, and local villagers. The results of this study show that village funds have a positive impact. Maranata village can be said to have increased in terms of infrastructure development and Community Empowerment. One of the positive impacts that has been felt by the community is the ease of access in everyday life. Village funds received by the village government are distributed in stages in accordance with applicable regulations and are divided into expenditure items for the field of village development and Community Empowerment. With a consistent village government in village deliberations, the village fund goals are achieved and Village development and community empowerment are carried out properly and effectively. This development was carried out on target and received support from the local community